DETERMINAN NILAI PERUSAHAAN PROPERTI DAN REAL ESTATE DI BURSA EFEK INDONESIA - Nurhasanah, Devy Ai; Metta Kusumaningtyas, Metta (ECONBANK: Journal of Economics and Banking, 2020)
This study aims to examine the effect of profitability, leverage, company size, and dividend policy on firm value. This research was conducted on property and real estate companies listed on the Indonesia Stock Exchange (IDX) for the period 2013-2017. The data used in this study are secondary data obtained from annual financial statements. The research method was carried out using multiple linear regression and sample selection using a purposive sampling method. Samples obtained as many as 114 companies in the period 2013-2017. The results showed that profitability and dividend policy had a positive effect on firm value. Likewise, leverage has a negative effect on firm value. Sometimes the size of the company does not affect the value of the company.